Побудова представлення знань на основі фактор графу з урахуванням частоти доступу до його вершин - Дородних, Д. О. (ХНУРЕ, 2023)
In today's fast-paced world, everyone wants easy access to accurate information. Users would rather use knowledge base and find an immediate solution to their problems than contact the help desk. Formal representation of knowledge bases is usually based on the use of graphs. One of the important areas of development of knowledge is the construction of factor graphs. The factor graph concept is used, in particular, in the DeepDive knowledge base. However, the existing architecture does not consider the frequency of use of the vertices of the graph. The proposed combined method increases the efficiency of the graph knowledge base built on factor graphs.